2019
DOI: 10.3390/met9090986
|View full text |Cite
|
Sign up to set email alerts
|

Green Preparation and Dry Sliding Wear Properties of a Macro-ZTA/Fe Composite Produced by a Two-Step Method

Abstract: In this paper, a two-step method, rapid-flow mixing followed by high-pressure compositing was used to prepare a macro-ZTA (ZrO2-toughened Al2O3) particles reinforced high chromium cast iron (HCCI) matrix composite. The method is based on the squeeze casting process without general casting pollution problems. The microstructure, mechanical properties and dry sliding wear performance of the fabricated composite were investigated. The results showed that the particles were distributed uniformly throughout the iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The new sands were replaced after each test duration to eliminate the 'size effect' of the abrasive sand. The mass changes before and after test were used for evaluating the wear resistance of the samples [9,11,18,[21][22][23][32][33][34]. The mass loss was the average value of three group experimental data to guarantee reproducibility.…”
Section: Three-body Abrasive Wear Test and Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…The new sands were replaced after each test duration to eliminate the 'size effect' of the abrasive sand. The mass changes before and after test were used for evaluating the wear resistance of the samples [9,11,18,[21][22][23][32][33][34]. The mass loss was the average value of three group experimental data to guarantee reproducibility.…”
Section: Three-body Abrasive Wear Test and Characterisationmentioning
confidence: 99%
“…On the other hand, the favourable fabrication technique can also improve the wear resistance of composites [33,34]. Qiu et al [33] found that the relative wear resistance of the ZTA reinforced Cr26-based composites prepared by pressure casting was higher than that of the composites prepared by infiltration casting due to their tight interfacial bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… The worn surface morphology of ZrO 2 -toughened Al 2 O 3 particles reinforced high-chromium cast iron (HCCI) matrix composite at different loads: ( a ) 300 N-low magnification; ( b ) 300 N-high magnification; ( c ) 900 N-low magnification; and ( d ) 300 N-high magnification [ 32 ]. …”
Section: Mechanisms Of Frictional Energy Dissipation On An Atomic mentioning
confidence: 99%
“…It is therefore necessary to develop composites with a low cost, a low friction coefficient, and a high wear resistance at elevated temperatures. Fe matrix material is one of the superalloys, which are widely used in many industrial fields as wear resistant mechanical parts [4,5]. High-temperature Fe matrix sleeves and bears always run at 600 • C. However, wear resistance depends on the mechanical properties of materials at elevated temperatures [6,7], resulting in severe wear.…”
Section: Introductionmentioning
confidence: 99%